Greenwashing, ESG Fraud, and the Forensic Gap: A Bibliometric Mapping - Dien Ajeng Fauziah; Syafii Syafii; Khoirul Abidin; Bambang Agoes Hermanto (LPPM Universitas KH A. Wahab Hasbullah, 2026)
The proliferation of ESG disclosures has been accompanied by rising concerns over greenwashing and sustainability-related fraud, yet the intellectual convergence of greenwashing, ESG fraud, and forensic accounting remains systematically unmapped. This study aims to map the intellectual structure, thematic evolution, and research frontiers at the intersection of sustainability misconduct and forensic accountability. Employing a Bibliometric, 1,285 Scopus-indexed journal articles published between 2007 and 2026 were analyzed using Biblioshiny. Techniques included performance analysis, keyword co-occurrence mapping, thematic mapping, and thematic evolution analysis. The co-occurrence network reveals four keyword clusters greenwashing and corporate legitimacy, corporate greenwashing in the green economy, ESG greenwashing and financing constraints, and governance and performance with the field demonstrating a 35.22% annual growth rate and projected peak output by 2032. Critically, forensic accounting remains conspicuously absent as a distinct thematic cluster, with the literature treating greenwashing primarily as a communication failure rather than a domain requiring investigative methodology. These findings empirically validate calls for integrative theoretical frameworks and define a future research agenda organized around five interconnected gaps: forensic integration, causal mechanisms, generalizability, forward-looking assurance, and detection methodology. The study provides the first data-grounded mapping of this interdisciplinary convergence, charting a pathway from the conceptual recognition of greenwashing toward actionable forensic investigation.